A multi-layer composite wedge-shaped splitter and a preparation method thereof

By adopting a multi-layer composite structure of wedge-shaped splitter knife, including tungsten steel rod, intermediate buffer layer and ceramic functional layer, the wear and fracture of traditional wedge-shaped splitter knife is solved, and the performance and service life are significantly improved.

CN119208152BActive Publication Date: 2025-04-11苏州芯合半导体材料有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411306055.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-04-11
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

Traditional single-material wedge-shaped choppers are prone to wear and breaking during long-term use, affecting packaging quality and production efficiency.

Method used

A wedge-shaped splitter using a multi-layer composite structure includes a tungsten steel rod, an intermediate buffer layer and a ceramic functional layer arranged in sequence from bottom to top. The elastic modulus and thermal expansion coefficient of the intermediate buffer layer are between the tungsten steel rod and the ceramic functional layer.

Benefits of technology

It significantly improves the overall performance and service life of the wedge-shaped chopper. The Mohs hardness can be as high as 9-9.5, the Vickers hardness can be as high as 30-35GPa, the fracture toughness can reach 6-8MPa·m^1/2, and it has excellent wear resistance and wear rate as low as 10^-6mm3/Nm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208152B_ABST
    Figure CN119208152B_ABST
Patent Text Reader

Abstract

The present invention discloses a multi-layer composite wedge-shaped splitting tool and a preparation method thereof. The wedge-shaped splitting tool comprises a tungsten steel rod, an intermediate buffer layer and a ceramic functional layer arranged in sequence from bottom to top. The elastic modulus of the intermediate buffer layer is between the elastic modulus of the tungsten steel rod and the ceramic functional layer, and the thermal expansion coefficient is between the thermal expansion coefficients of the tungsten steel rod and the ceramic functional layer. The multi-layer composite wedge-shaped splitting tool and the preparation method thereof provided by the present invention improve the overall performance and service life of the wedge-shaped splitting tool by designing the composite structure of the tungsten steel rod, the intermediate buffer layer and the ceramic functional layer. The Mohs hardness of the wedge-shaped splitting tool can be as high as 9-9.5, and the Vickers hardness can be as high as 30-35GPa, which is close to diamond. The fracture toughness can reach 6-8MPa·m^1 / 2. The wedge-shaped splitting tool also exhibits excellent wear resistance, and the wear rate is as low as 10^-6mm 3 / Nm, suitable for promotion and application in semiconductor packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor packaging, and in particular relates to a multi-layer composite wedge-shaped splitting tool and a preparation method thereof. Background Art

[0002] In the semiconductor packaging process, the wedge-shaped splitter is an important tool for cutting and forming lead frames. Traditional wedge-shaped splitters are usually made of a single material such as tungsten steel. Although they have a certain hardness and wear resistance, they are prone to wear and breakage during long-term use, affecting packaging quality and production efficiency. Therefore, it is of great significance to develop a wedge-shaped splitter with a longer service life. Summary of the invention

[0003] In order to solve the technical problems existing in the prior art, the object of the present invention is to provide a multi-layer composite wedge-shaped splitter and a preparation method thereof.

[0004] In order to achieve the above purpose and the above technical effect, the technical solution adopted by the present invention is:

[0005] A multi-layer composite wedge-shaped splitting tool comprises a tungsten steel rod, an intermediate buffer layer and a ceramic functional layer which are arranged in sequence from bottom to top. The elastic modulus of the intermediate buffer layer is between the elastic moduli of the tungsten steel rod and the ceramic functional layer, and the thermal expansion coefficient of the intermediate buffer layer is between the thermal expansion coefficients of the tungsten steel rod and the ceramic functional layer.

[0006] Furthermore, the composition of the tungsten steel rod is WC-10Co, and the hardness is HRA89-91.

[0007] Furthermore, the intermediate buffer layer is made of Ti-6Al-4V titanium alloy and has a thickness of 0.5-1 mm.

[0008] Furthermore, the ceramic functional layer is made of boron nitride, aluminum oxide and zirconium oxide, and has a thickness of 0.2-0.6 mm.

[0009] Furthermore, the preparation steps of the tungsten steel rod include:

[0010] The WC powder and the Co powder are put into a ball mill at a weight ratio of 80-95:5-20 for ball milling for 24-48 hours, the ball-to-material ratio is 3:1-5:1, the average particle size of the WC powder is 1-5μm, and the average particle size of the Co powder is 1-3μm; after being taken out, they are dried at 60-80℃ for 12-24 hours, and then sent to a spray granulator for granulation to obtain mixed particles with a particle size of 100-200μm, and then molded, degreased, pre-sintered, sintered, and post-treated in sequence, and then tungsten steel rods are formed by mechanical processing according to the size of the wedge-shaped splitter.

[0011] Furthermore, the molding is performed by cold isostatic pressing, and the molding parameters are as follows:

[0012] The molding pressure is 200-300MPa, and the holding time is 1-2min;

[0013] The parameters for degreasing are:

[0014] The degreasing temperature is 300-400℃, the degreasing time is 1-2h, and the atmosphere is hydrogen or vacuum;

[0015] The parameters of pre-sintering are:

[0016] The pre-sintering temperature is 800-1000℃, the pre-sintering time is 30-60min, and the atmosphere is vacuum or hydrogen;

[0017] The sintering parameters are:

[0018] The sintering temperature is 1350-1500℃, the sintering time is 60-120min, the atmosphere is vacuum or hydrogen, the heating rate is 5-10℃ / min, and the cooling rate is natural cooling;

[0019] The post-processing parameters are:

[0020] Hot isostatic pressing, temperature is 1300-1400℃, pressure is 100-200MPa, time is 1-2h.

[0021] Furthermore, the preparation step of the intermediate buffer layer includes:

[0022] Ti, Al and V are mixed and smelted in a weight ratio of 87-92:5-8:3-5 to obtain an ingot with a diameter of 400-600 mm, which is cooled at a cooling rate of 50-100°C / min, and then homogenized heat treatment, forging, annealing, machining, solution treatment and aging treatment are carried out in sequence to obtain Ti-6Al-4V titanium alloy.

[0023] Furthermore, vacuum consumable arc melting is performed, and the melting parameter conditions are:

[0024] The melting temperature is 1650-1700℃, the melting pressure is <0.1Pa, and the melting time is 2-3h;

[0025] The parameters of homogenization heat treatment are:

[0026] The heat treatment temperature is 1000-1050℃, the heat treatment time is 1-2h, and the cooling method is furnace cooling;

[0027] The forging parameters are:

[0028] Starting temperature 950-1000℃, ending temperature 700-750℃, deformation 60-70%;

[0029] The annealing parameters are:

[0030] The annealing temperature is 700-750℃, the annealing time is 1-2h, and the cooling method is air cooling;

[0031] The machining parameters are:

[0032] Cutting speed is 30-60m / min;

[0033] Feed rate is 0.1-0.3mm / r;

[0034] The parameters of solution treatment are:

[0035] The treatment temperature is 955-970℃, the treatment time is 0.5-2h, and the cooling method is water cooling;

[0036] The parameter conditions for aging treatment are:

[0037] The processing temperature is 480-495°C, the processing time is 6-8h, and the cooling method is air cooling.

[0038] Furthermore, the steps of preparing the ceramic functional layer include:

[0039] According to the weight ratio, 40-50wt% of boron nitride, 30-40wt% of aluminum oxide, and 10-20wt% of zirconium oxide are put into a ball mill for ball milling for 4-6 hours at a speed of 200-250rpm, and then an organic binder is added, heated and mixed at 160-180°C for 1-2 hours, and then granulated to obtain ceramic particles with a particle size of 2-3mm;

[0040] The obtained ceramic particles are then injection molded at an injection temperature of 160-180°C, an injection pressure of 80-120MPa, a holding time of 10-15s, and a cooling time of 30-40s;

[0041] Then degreasing is carried out, the degreasing temperature is 500-700℃, the degreasing time is 20-30h, the heating rate is 0.5-1℃ / min, the maximum temperature is 700℃, and the heat preservation is 2-3h;

[0042] Then sintering is performed, the heating rate is 3-5°C / min, the sintering temperature is 1700-1800°C, the holding time is 2-3h, the cooling rate is 5-10°C / min, and the sintering atmosphere is nitrogen or vacuum;

[0043] Finally, the required ceramic functional layer is obtained by electrospark discharge machining.

[0044] The present invention also discloses a method for preparing a multi-layer composite wedge-shaped splitter, comprising the following steps:

[0045] S1. Prepare tungsten steel rod;

[0046] S2, preparing Ti-6Al-4V titanium alloy;

[0047] S3, preparing a ceramic functional layer;

[0048] S4. Weld the tungsten steel rod and Ti-6Al-4V titanium alloy together. The welding parameters are as follows:

[0049] The welding frequency is 20-40kHz, the welding amplitude is 10-100μm, the pressure applied during welding is 5-10kN, and the welding time is 1-5s;

[0050] S5. Braze the Ti-6Al-4V titanium alloy and the ceramic functional layer together through titanium-based active brazing filler metal, the steps are as follows:

[0051] S51, surface treatment: grinding Ti-6Al-4V titanium alloy to 600-800# to form a rough surface, and sandblasting or chemically etching the ceramic functional layer to increase the surface roughness;

[0052] S52, solder preparation: titanium-based active solder and organic binder are mixed evenly, and then screen-printed or sprayed on the surface of Ti-6Al-4V titanium alloy and ceramic functional layer, with a thickness of 10-50 μm;

[0053] S53, Brazing: Brazing is carried out at 900-980℃ under vacuum or inert gas atmosphere, with a heating rate of 10℃ / min, a holding time of 10-20min, a cooling rate of 5-10℃ / min or natural cooling;

[0054] S54, post-processing.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] The invention discloses a multi-layer composite wedge-shaped splitter and a preparation method thereof. The overall performance and service life of the wedge-shaped splitter are improved by designing a composite structure of a tungsten steel rod, an intermediate buffer layer, and a ceramic functional layer. The Mohs hardness of the wedge-shaped splitter can be as high as 9-9.5, and the Vickers hardness can be as high as 30-35GPa, which is close to diamond. The fracture toughness can reach 6-8MPa·m^1 / 2. The wedge-shaped splitter also exhibits excellent wear resistance, and the wear rate is as low as 10^-6mm 3 / Nm, suitable for promotion and application in semiconductor packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1It is a schematic structural diagram of the wedge-shaped splitter of the present invention. DETAILED DESCRIPTION

[0058] The present invention is described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0059] A brief summary of one or more aspects is given below to provide a basic understanding of these aspects. This summary is not an exhaustive overview of all conceived aspects, and is neither intended to identify the key or critical elements of all aspects nor to define the scope of any or all aspects. Its only purpose is to give some concepts of one or more aspects in a simplified form as a prelude to a more detailed description that will be given later.

[0060] like Figure 1 As shown, the present invention discloses a multi-layer composite wedge-shaped splitting cutter, comprising a tungsten steel rod, an intermediate buffer layer and a ceramic functional layer which are arranged in sequence from bottom to top.

[0061] The composition of tungsten steel rod is WC-10Co, with hardness of HRA 89-91.

[0062] The middle buffer layer is made of Ti-6Al-4V titanium alloy with a thickness of 0.5-1mm. The reason for placing it between the tungsten steel rod and the ceramic functional layer is:

[0063] The elastic modulus of Ti-6Al-4V titanium alloy is between that of tungsten steel rod and ceramic functional layer, so it can alleviate the stress mismatch between the two materials of tungsten steel rod and ceramic functional layer and reduce stress concentration;

[0064] The thermal expansion coefficient of Ti-6Al-4V titanium alloy is between that of the tungsten steel rod and the ceramic functional layer, thus reducing thermal stress;

[0065] Ti-6Al-4V titanium alloy has good bonding with tungsten steel rod and ceramic functional layer, which can improve the overall bonding strength of the wedge-shaped splitter;

[0066] The overall toughness of the wedge cutter can be improved and the risk of brittle fracture can be reduced.

[0067] The ceramic functional layer is made of boron nitride (BN) + aluminum oxide (Al2O3) + zirconium oxide (ZrO2) with a thickness of 0.2-0.6mm. Due to the combination of the high hardness of BN and Al2O3, the Mohs hardness of the wedge-shaped splitter can be as high as 9-9.5, and the Vickers hardness can be as high as 30-35GPa, which is close to diamond. At the same time, due to the addition of ZrO2, the fracture toughness of the wedge-shaped splitter is significantly improved, up to 6-8MPa·m^1 / 2. The wedge-shaped splitter also exhibits excellent wear resistance, with a wear rate as low as 10^-6mm3 / Nm.

[0068] The present invention significantly improves the overall performance (including hardness, toughness, etc.) and service life of the wedge-shaped splitting cutter by adopting a tungsten steel rod, an intermediate buffer layer and a ceramic functional layer structure design.

[0069] The preparation steps of tungsten steel rod include:

[0070] 1) Raw material preparation

[0071] WC powder: average particle size 1-5μm;

[0072] Co powder: average particle size 1-3 μm;

[0073] Ratio: 80-95% WC + 2-20% Co (weight ratio);

[0074] 2) Mixing

[0075] Equipment: ball mill;

[0076] Mixing time: 24-48h;

[0077] Medium: anhydrous ethanol or acetone;

[0078] Ball-to-material ratio: 3:1-5:1;

[0079] 3) Drying

[0080] Equipment: vacuum drying oven;

[0081] Drying temperature: 60-80℃;

[0082] Drying time: 12-24h;

[0083] 4) Granulation

[0084] Equipment: spray granulator;

[0085] Particle size: 100-200 μm;

[0086] Additives: polyethylene glycol PEG 0.5-1.5%;

[0087] 5) Molding

[0088] Method: Cold isostatic pressing

[0089] Pressure: 200-300MPa;

[0090] Holding time: 1-2min;

[0091] 6) Degreasing

[0092] Temperature: 300-400℃;

[0093] Time: 1-2 hours;

[0094] Atmosphere: hydrogen or vacuum;

[0095] 7) Pre-sintering

[0096] Temperature: 800-1000℃;

[0097] Time: 30-60min;

[0098] Atmosphere: vacuum or hydrogen;

[0099] 8) Sintering

[0100] Temperature: 1350-1500℃;

[0101] Time: 60-120min;

[0102] Atmosphere: vacuum or hydrogen;

[0103] Heating rate: 5-10℃ / min;

[0104] Cooling rate: natural cooling;

[0105] 9) Post-processing

[0106] Hot isostatic pressing (HIP);

[0107] Temperature: 1300-1400℃;

[0108] Pressure: 100-200MPa;

[0109] Time: 1-2 hours;

[0110] 10) According to the size of the wedge-shaped splitter, the tungsten steel rod is formed by mechanical processing. The preparation steps of the intermediate buffer layer include:

[0111] 1) Raw material preparation

[0112] Raw materials: titanium sponge, aluminum, vanadium, etc.;

[0113] Composition ratio: Ti 87-92%, Al 5-8%, V 3-5% (weight ratio);

[0114] 2) Melting

[0115] Method: Vacuum consumable arc melting VAR;

[0116] Temperature: 1650-1700℃;

[0117] Pressure: <0.1Pa;

[0118] Time: 2-3 hours;

[0119] 3) Ingot

[0120] Ingot diameter: 400-600mm;

[0121] Cooling rate: 50-100℃ / min;

[0122] 4) Homogenization heat treatment

[0123] Temperature: 1000-1050℃;

[0124] Time: 1-2 hours;

[0125] Cooling: furnace cooling;

[0126] 5) Forging

[0127] Starting temperature: 950-1000℃;

[0128] Termination temperature: 700-750℃;

[0129] Deformation: 60-70%;

[0130] 6) Annealing

[0131] Temperature: 700-750℃;

[0132] Time: 1-2 hours;

[0133] Cooling: air cooling;

[0134] 7) Machining

[0135] Cutting speed: 30-60m / min;

[0136] Feed rate: 0.1-0.3mm / r;

[0137] 8) Solution treatment

[0138] Temperature: 955-970℃;

[0139] Time: 0.5-2h;

[0140] Cooling: water cooling;

[0141] 9) Aging treatment

[0142] Temperature: 480-495℃;

[0143] Time: 6-8h;

[0144] Cooling: air cooling.

[0145] The ceramic functional layer is made by injection molding, and the preparation steps include:

[0146] 1) Powder mixing process and parameters Raw material ratio: boron nitride 40-50wt%, aluminum oxide 30-40wt%, zirconium oxide 10-20wt%;

[0147] Ball milling: use planetary ball mill, ball to material ratio 1:4, speed 200-250rpm, time 4-6h; add organic binder: polyethylene 15-20vol%, paraffin 5-10vol%, lubricant 1-2vol%;

[0148] Hot mixing: temperature 160-180℃, time 1-2h;

[0149] Granulation to produce ceramic particles with a particle size of 2-3 mm;

[0150] 2) Injection molding parameters

[0151] Injection temperature: 160-180℃;

[0152] Injection pressure: 80-120MPa;

[0153] Mold temperature: 40-60℃;

[0154] Holding time: 10-15s;

[0155] Cooling time: 30-40s;

[0156] 3) Degreasing parameters

[0157] Solvent degreasing: use n-hexane, temperature 500-700℃, time 20-30h;

[0158] Thermal degreasing: heating rate 0.5-1℃ / min, maximum temperature 700℃, heat preservation 2-3h;

[0159] 4) Sintering parameters

[0160] Heating rate: 3-5℃ / min;

[0161] Sintering temperature: 1700-1800℃;

[0162] Insulation time: 2-3h;

[0163] Cooling rate: 5-10℃ / min;

[0164] Sintering atmosphere: nitrogen or vacuum;

[0165] 5) Using electric spark discharge to obtain the required ceramic functional layer.

[0166] The present invention also discloses a method for preparing a multi-layer composite wedge-shaped splitter, comprising the following steps:

[0167] S1. Prepare tungsten steel rod;

[0168] S2, preparing Ti-6Al-4V titanium alloy;

[0169] S3, preparing a ceramic functional layer;

[0170] S4, welding the tungsten steel rod and Ti-6Al-4V titanium alloy together;

[0171] S5. Braze the Ti-6Al-4V titanium alloy and the ceramic functional layer together through titanium-based active brazing filler metal. The main components of the titanium-based active brazing filler metal usually include:

[0172] Titanium Ti is an active metal that can form a good chemical bond with ceramics and is a key component for brazing Ti-6Al-4V titanium alloy and ceramic functional layer;

[0173] Copper Cu or silver Ag, copper or silver is a low melting point metal, which can reduce the melting temperature of the solder and improve the liquid phase diffusion capacity;

[0174] Active elements, usually adding a small amount of active elements such as aluminum and silicon to improve the wettability and reactivity of the brazing material and ceramics;

[0175] In addition, the solder may also contain other elements such as transition metals such as tantalum and vanadium to adjust the physical and chemical properties of the solder.

[0176] The main advantages of using titanium-based active brazing filler metals include: good thermal expansion matching with Ti-6Al-4V titanium alloy, which can reduce residual stress; titanium has excellent corrosion resistance, which can improve the corrosion resistance of brazed joints; titanium and ceramics can form chemical bonds, and the brazed joints have high strength and good reliability; the brazing filler metal composition can be adjusted to meet different application requirements.

[0177] In step S4, the step of welding the tungsten steel rod and the Ti-6Al-4V titanium alloy together includes:

[0178] S41. Preparation

[0179] Clean the surface of Ti-6Al-4V titanium alloy and tungsten steel rod to be welded to remove oil, oxides and other contaminants;

[0180] Determine the welding area and ensure that the welding surface is flat and free of defects;

[0181] S42, welding parameter setting

[0182] Frequency: 20-40kHz;

[0183] Amplitude: 10-100 μm;

[0184] Pressure: The pressure applied during welding is 5-10kN;

[0185] Welding time: 1-5s;

[0186] S43, welding process

[0187] Place the Ti-6Al-4V titanium alloy and tungsten steel rod in the fixture of the ultrasonic welding machine to ensure that the welding surfaces are in close contact;

[0188] Turn on the ultrasonic generator and apply a predetermined amplitude and pressure;

[0189] Maintain vibration and pressure until plastic deformation occurs on the material surface to form a welded joint;

[0190] S44, post-weld treatment

[0191] Check the welded joints to ensure there are no defects such as cracks and holes;

[0192] Post-weld heat treatment is performed to eliminate internal stress and improve joint performance.

[0193] In step S5, the step of brazing the Ti-6Al-4V titanium alloy and the ceramic functional layer together by using a titanium-based active brazing filler metal comprises:

[0194] S51, surface treatment

[0195] Grind the Ti-6Al-4V titanium alloy to 600-800# to form a rough surface, and sandblast or chemically etch the ceramic functional layer to increase the surface roughness;

[0196] S52. Preparation of solder

[0197] The titanium-based active brazing filler metal is mixed evenly with the organic binder by gas atomization or mechanical alloying, and then screen-printed or sprayed on the surface of the Ti-6Al-4V titanium alloy and the ceramic functional layer with a thickness of 10-50μm;

[0198] S53, Brazing

[0199] Brazing is performed at 900-980℃ under vacuum or inert gas atmosphere, with a heating rate of 10-20℃ / min, a holding time of 10-20min, a cooling rate of 5-10℃ / min or natural cooling;

[0200] S54, post-processing

[0201] Heat treatment: aging or annealing to improve mechanical properties;

[0202] Machining: removing excess solder, etc.

[0203] Example 1

[0204] like Figure 1As shown, a multi-layer composite wedge-shaped splitting tool includes a tungsten steel rod, an intermediate buffer layer and a ceramic functional layer arranged in sequence from bottom to top.

[0205] The composition of tungsten steel rod is WC-10Co, with hardness of HRA 90.

[0206] The middle buffer layer is made of Ti-6Al-4V titanium alloy with a thickness of 0.5 mm.

[0207] The ceramic functional layer is made of boron nitride (BN) + aluminum oxide (Al2O3) + zirconium oxide (ZrO2) with a thickness of 0.2mm. The preparation steps of tungsten steel rod include:

[0208] 1) Raw material preparation

[0209] WC powder: average particle size 2μm;

[0210] Co powder: average particle size 2 μm;

[0211] Ratio: 88% WC + 2% Co (weight ratio);

[0212] 2) Mixing

[0213] Equipment: ball mill;

[0214] Mixing time: 24h;

[0215] Medium: anhydrous ethanol;

[0216] Ball-to-material ratio: 3:1;

[0217] 3) Drying

[0218] Equipment: vacuum drying oven;

[0219] Drying temperature: 60℃;

[0220] Drying time: 12h;

[0221] 4) Granulation

[0222] Equipment: spray granulator;

[0223] Particle size: 100 μm;

[0224] Additives: polyethylene glycol PEG 0.5%;

[0225] 5) Molding

[0226] Method: Cold isostatic pressing

[0227] Pressure: 200MPa;

[0228] Holding time: 1min;

[0229] 6) Degreasing

[0230] Temperature: 300℃;

[0231] Time: 1h;

[0232] Atmosphere: hydrogen or vacuum;

[0233] 7) Pre-sintering

[0234] Temperature: 800℃;

[0235] Time: 30 minutes;

[0236] Atmosphere: vacuum;

[0237] 8) Sintering

[0238] Temperature: 1350℃;

[0239] Time: 60 minutes;

[0240] Atmosphere: vacuum;

[0241] Heating rate: 5℃ / min;

[0242] Cooling rate: natural cooling;

[0243] 9) Post-processing

[0244] Hot isostatic pressing (HIP);

[0245] Temperature: 1300℃;

[0246] Pressure: 100MPa;

[0247] Time: 1h;

[0248] 10) According to the size of the wedge-shaped splitter, the tungsten steel rod is formed by mechanical processing. The preparation steps of the intermediate buffer layer include:

[0249] 1) Raw material preparation

[0250] Raw materials: titanium sponge, aluminum, vanadium, etc.;

[0251] Composition ratio: Ti 87%, Al 8%, V 5% (weight ratio);

[0252] 2) Melting

[0253] Method: Vacuum consumable arc melting VAR;

[0254] Temperature: 1650℃;

[0255] Pressure: <0.1Pa;

[0256] Time: 2h;

[0257] 3) Ingot

[0258] Ingot diameter: 400mm;

[0259] Cooling rate: 50℃ / min;

[0260] 4) Homogenization heat treatment

[0261] Temperature: 1000℃;

[0262] Time: 1h;

[0263] Cooling: furnace cooling;

[0264] 5) Forging

[0265] Starting temperature: 950℃;

[0266] Termination temperature: 700℃;

[0267] Deformation: 60%;

[0268] 6) Annealing

[0269] Temperature: 700℃;

[0270] Time: 1h;

[0271] Cooling: air cooling;

[0272] 7) Machining

[0273] Cutting speed: 30m / min;

[0274] Feed rate: 0.1mm / r;

[0275] 8) Solution treatment

[0276] Temperature: 955℃;

[0277] Time: 0.5h;

[0278] Cooling: water cooling;

[0279] 9) Aging treatment

[0280] Temperature: 480℃;

[0281] Time: 6h;

[0282] Cooling: air cooling.

[0283] The ceramic functional layer is made by injection molding, and the preparation steps include:

[0284] 1) Powder mixing process and parameters Raw material ratio: boron nitride 40wt%, aluminum oxide 40wt%, zirconium oxide 20wt%;

[0285] Ball milling: using a planetary ball mill, ball-to-material ratio 1:4, speed 200 rpm, time 4 h; adding organic binder: polyethylene 20 vol%, paraffin 5 vol%, lubricant 2 vol%;

[0286] Hot mixing: temperature 160°C, time 1h;

[0287] Granulation to produce ceramic particles with a particle size of 2 mm;

[0288] 2) Injection molding parameters

[0289] Injection temperature: 160℃;

[0290] Injection pressure: 80MPa;

[0291] Mold temperature: 40℃;

[0292] Holding time: 10s;

[0293] Cooling time: 30s;

[0294] 3) Degreasing parameters

[0295] Solvent degreasing: use n-hexane, temperature 500℃, time 20h;

[0296] Thermal degreasing: heating rate 0.5℃ / min, maximum temperature 700℃, heat preservation 2h;

[0297] 4) Sintering parameters

[0298] Heating rate: 3℃ / min;

[0299] Sintering temperature: 1700℃;

[0300] Insulation time: 2h;

[0301] Cooling rate: 5℃ / min;

[0302] Sintering atmosphere: vacuum;

[0303] 5) Using electric spark discharge to obtain the required ceramic functional layer.

[0304] A method for preparing a multi-layer composite wedge-shaped splitter comprises the following steps:

[0305] S1. Prepare tungsten steel rod;

[0306] S2, preparing Ti-6Al-4V titanium alloy;

[0307] S3, preparing a ceramic functional layer;

[0308] S4, welding the tungsten steel rod and Ti-6Al-4V titanium alloy together;

[0309] S5. Braze the Ti-6Al-4V titanium alloy and the ceramic functional layer together through titanium-based active brazing filler metal. The main components of the titanium-based active brazing filler metal usually include:

[0310] Titanium Ti is an active metal that can form a good chemical bond with ceramics and is a key component for brazing Ti-6Al-4V titanium alloy and ceramic functional layer;

[0311] Copper Cu, copper is a low melting point metal, which can reduce the melting temperature of the solder and improve the liquid phase diffusion capacity;

[0312] Active elements, usually a small amount of aluminum is added to improve the wettability and reactivity of the brazing filler metal and ceramics.

[0313] The main advantages of using titanium-based active brazing filler metals include: good thermal expansion matching with Ti-6Al-4V titanium alloy, which can reduce residual stress; titanium has excellent corrosion resistance, which can improve the corrosion resistance of brazed joints; titanium and ceramics can form chemical bonds, and the brazed joints have high strength and good reliability; the brazing filler metal composition can be adjusted to meet different application requirements.

[0314] In step S4, the step of welding the tungsten steel rod and the Ti-6Al-4V titanium alloy together includes:

[0315] S41. Preparation

[0316] Clean the surface of Ti-6Al-4V titanium alloy and tungsten steel rod to be welded to remove oil, oxides and other contaminants;

[0317] Determine the welding area and ensure that the welding surface is flat and free of defects;

[0318] S42, welding parameter setting

[0319] Frequency: 20kHz;

[0320] Amplitude: 10 μm;

[0321] Pressure: The pressure applied during welding is 5kN;

[0322] Welding time: 2s;

[0323] S43, welding process

[0324] Place the Ti-6Al-4V titanium alloy and tungsten steel rod in the fixture of the ultrasonic welding machine to ensure that the welding surfaces are in close contact;

[0325] Turn on the ultrasonic generator and apply a predetermined amplitude and pressure;

[0326] Maintain vibration and pressure until plastic deformation occurs on the material surface to form a welded joint;

[0327] S44, post-weld treatment

[0328] Check the welded joints to ensure there are no defects such as cracks and holes;

[0329] Post-weld heat treatment is performed to eliminate internal stress and improve joint performance.

[0330] In step S5, the step of brazing the Ti-6Al-4V titanium alloy and the ceramic functional layer together by using a titanium-based active brazing filler metal comprises:

[0331] S51, surface treatment

[0332] The Ti-6Al-4V titanium alloy is ground to 600# to form a rough surface, and the ceramic functional layer is sandblasted or chemically etched to increase the surface roughness;

[0333] S52. Preparation of solder

[0334] The titanium-based active brazing filler metal and the organic binder are mixed evenly by gas atomization or mechanical alloying, and then screen-printed or sprayed on the surface of the Ti-6Al-4V titanium alloy and the ceramic functional layer with a thickness of 10 μm.

[0335] S53, Brazing

[0336] Brazing is performed at 900°C in a vacuum or inert gas atmosphere, with a heating rate of 10°C / min, a holding time of 10min, a cooling rate of 5°C / min or natural cooling;

[0337] S54, post-processing

[0338] Heat treatment: aging or annealing to improve mechanical properties;

[0339] Machining: removing excess solder, etc.

[0340] Example 2

[0341] The difference between this embodiment and embodiment 1 is that the thickness of the ceramic functional layer in this embodiment is 0.4 mm. The rest is the same as embodiment 1.

[0342] Example 3

[0343] The difference between this embodiment and embodiment 1 is that the thickness of the ceramic functional layer in this embodiment is 0.6 mm. The rest is the same as embodiment 1.

[0344] Comparative Example 1

[0345] Commercially available pure tungsten steel rod.

[0346] Comparative Example 2

[0347] The difference between this comparative example and Example 1 is that this comparative example does not have a ceramic functional layer.

[0348] The rest is the same as in Example 1.

[0349] Comparative Example 3

[0350] The difference between this comparative example and Example 1 is that this comparative example has no intermediate buffer layer.

[0351] The rest is the same as in Example 1.

[0352] Comparative Example 4

[0353] The difference between this comparative example and Example 1 is that the thickness of the ceramic functional layer in this comparative example is 0.8 mm. The rest is the same as Example 1.

[0354] The structural compositions and performance results of Examples 1-3 and Comparative Examples 1-4 are shown in Table 1.

[0355] Table 1

[0356]

[0357]

[0358] From Table 1, we can see that:

[0359] The wear rate of Examples 1-3 is lower than that of Comparative Examples 1-4, and there are no stress cracks, and no ceramic functional layer falls off, showing excellent wear resistance. The wire bonding life of Examples 1-3 is higher than that of Comparative Examples 1-4, indicating that only by using the tungsten steel rod, the intermediate buffer layer and the ceramic functional layer disclosed in the present invention can a wedge-shaped splitter with a long life, low wear rate, no stress cracks, and no ceramic functional layer falling off be obtained. Only a tungsten steel rod or a tungsten steel rod + an intermediate buffer layer or a tungsten steel rod + a ceramic functional layer cannot obtain a wedge-shaped splitter with a long life, low wear rate, no stress cracks, and no ceramic functional layer falling off;

[0360] By comparing Examples 1-3 and Comparative Example 4, it can be seen that as the thickness of the ceramic functional layer increases from 0.2 mm to 0.6 mm, the wear of the wedge-shaped splitting cutter first decreases and then increases, and there are no stress cracks, and no ceramic functional layer shedding. When the thickness of the ceramic functional layer is 0.4 mm, the wear rate is the lowest. When the thickness of the ceramic functional layer is 0.8 mm, stress cracks appear and the ceramic functional layer is easily sheared off by external shear force, indicating that the thickness of the ceramic functional layer is not the larger the better. Only in the range of 0.2-0.6 mm can a wedge-shaped splitting cutter with a low wear rate, no stress cracks, and no ceramic functional layer shedding be obtained. A wedge-shaped splitting cutter with a low wear rate, no stress cracks, and no ceramic functional layer shedding cannot be obtained when the thickness exceeds 0.6 mm.

[0361] Parts or structures not specifically described in the present invention may adopt existing technologies or existing products and will not be described in detail here.

[0362] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A multi-layer composite wedge-shaped riving cutter, characterized in that: It includes a tungsten steel rod, an intermediate buffer layer and a ceramic functional layer arranged in sequence from bottom to top, wherein the elastic modulus of the intermediate buffer layer is between the elastic moduli of the tungsten steel rod and the ceramic functional layer, and the thermal expansion coefficient of the intermediate buffer layer is between the thermal expansion coefficients of the tungsten steel rod and the ceramic functional layer; The intermediate buffer layer is made of Ti-6Al-4V titanium alloy and has a thickness of 0.5-1 mm.

2. The multi-layer composite wedge-shaped riving cutter according to claim 1, characterized in that: The composition of the tungsten steel rod is WC-10Co, and the hardness is HRA89-91.

3. The multi-layer composite wedge-shaped riving cutter according to claim 1, characterized in that: The ceramic functional layer is made of boron nitride, aluminum oxide and zirconium oxide, and has a thickness of 0.2-0.6 mm.

4. The multi-layer composite wedge-shaped riving cutter according to claim 1, characterized in that: The preparation steps of the tungsten steel rod include: The WC powder and the Co powder are put into a ball mill at a weight ratio of 80-95:5-20 for ball milling for 24-48 hours, the ball-to-material ratio is 3:1-5:1, the average particle size of the WC powder is 1-5μm, and the average particle size of the Co powder is 1-3μm; after being taken out, they are dried at 60-80℃ for 12-24 hours, and then sent to a spray granulator for granulation to obtain mixed particles with a particle size of 100-200μm, and then molded, degreased, pre-sintered, sintered, and post-treated in sequence, and then tungsten steel rods are formed by mechanical processing according to the size of the wedge-shaped splitter.

5. The multi-layer composite wedge-shaped riving cutter according to claim 4, characterized in that: The molding parameters are as follows: The molding pressure is 200-300MPa, and the holding time is 1-2min; The parameters for degreasing are: The degreasing temperature is 300-400℃, the degreasing time is 1-2h, and the atmosphere is hydrogen or vacuum; The parameters of pre-sintering are: The pre-sintering temperature is 800-1000℃, the pre-sintering time is 30-60min, and the atmosphere is vacuum or hydrogen; The sintering parameters are: The sintering temperature is 1350-1500℃, the sintering time is 60-120min, the atmosphere is vacuum or hydrogen, the heating rate is 5-10℃ / min, and the cooling rate is natural cooling; The post-processing parameters are: Hot isostatic pressing, temperature is 1300-1400℃, pressure is 100-200MPa, time is 1-2h.

6. The multi-layer composite wedge-shaped riving cutter according to claim 1, characterized in that: The steps of preparing the intermediate buffer layer include: Ti, Al and V are mixed and smelted in a weight ratio of 87-92:5-8:3-5 to obtain an ingot with a diameter of 400-600 mm, which is cooled at a cooling rate of 50-100°C / min, and then homogenized heat treatment, forging, annealing, machining, solution treatment and aging treatment are carried out in sequence to obtain Ti-6Al-4V titanium alloy.

7. The multi-layer composite wedge-shaped riving cutter according to claim 6, characterized in that: Through vacuum consumable arc melting, the melting parameters are: The melting temperature is 1650-1700℃, the melting pressure is <0.1Pa, and the melting time is 2-3h; The parameters of homogenization heat treatment are: The heat treatment temperature is 1000-1050℃, the heat treatment time is 1-2h, and the cooling method is furnace cooling; The forging parameters are: Starting temperature 950-1000℃, ending temperature 700-750℃, deformation 60-70%; The annealing parameters are: The annealing temperature is 700-750℃, the annealing time is 1-2h, and the cooling method is air cooling; The machining parameters are: Cutting speed is 30-60m / min; Feed rate is 0.1-0.3mm / r; The parameters of solution treatment are: The treatment temperature is 955-970℃, the treatment time is 0.5-2h, and the cooling method is water cooling; The parameter conditions for aging treatment are: The processing temperature is 480-495°C, the processing time is 6-8h, and the cooling method is air cooling.

8. The multi-layer composite wedge-shaped riving cutter according to claim 1, characterized in that: The steps of preparing the ceramic functional layer include: According to the weight ratio, 40-50wt% of boron nitride, 30-40wt% of aluminum oxide, and 10-20wt% of zirconium oxide are put into a ball mill for ball milling for 4-6 hours at a speed of 200-250rpm, and then an organic binder is added, heated and mixed at 160-180°C for 1-2 hours, and then granulated to obtain ceramic particles with a particle size of 2-3mm; The obtained ceramic particles are then injection molded at an injection temperature of 160-180°C, an injection pressure of 80-120MPa, a holding time of 10-15s, and a cooling time of 30-40s; Then degreasing is carried out, the degreasing temperature is 500-700℃, the degreasing time is 20-30h, the heating rate is 0.5-1℃ / min, the maximum temperature is 700℃, and the heat preservation is 2-3h; Then sintering is performed, the heating rate is 3-5°C / min, the sintering temperature is 1700-1800°C, the holding time is 2-3h, the cooling rate is 5-10°C / min, and the sintering atmosphere is nitrogen or vacuum; Finally, the required ceramic functional layer is obtained by electrospark discharge machining.

9. The method for preparing a multi-layer composite wedge-shaped splitter according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Prepare tungsten steel rod; S2, preparing Ti-6Al-4V titanium alloy; S3, preparing a ceramic functional layer; S4. Weld the tungsten steel rod and Ti-6Al-4V titanium alloy together. The welding parameters are as follows: The welding frequency is 20-40kHz, the welding amplitude is 10-100μm, the pressure applied during welding is 5-10kN, and the welding time is 1-5s; S5. Braze the Ti-6Al-4V titanium alloy and the ceramic functional layer together through titanium-based active brazing filler metal, the steps are as follows: S51, surface treatment: grinding Ti-6Al-4V titanium alloy to 600-800# to form a rough surface, and sandblasting or chemically etching the ceramic functional layer to increase the surface roughness; S52, solder preparation: titanium-based active solder and organic binder are mixed evenly, and then screen-printed or sprayed on the surface of Ti-6Al-4V titanium alloy and ceramic functional layer, with a thickness of 10-50 μm; S53, Brazing: Brazing is carried out at 900-980℃ under vacuum or inert gas atmosphere, with a heating rate of 10℃ / min, a holding time of 10-20min, a cooling rate of 5-10℃ / min or natural cooling; S54, post-processing.

Citation Information

Patent Citations

  • Chopping knife for microelectronic bonding and processing method thereof

    CN115799094A

  • Low-friction wedge-shaped thick wire chopper

    CN220829928U